2016
DOI: 10.3109/10826084.2015.1110176
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Stress, Negative Emotions, Resilience, and Smoking: Testing a Moderated Mediation Model

Abstract: Objective More effective tobacco prevention and cessation programs require in-depth understanding of the mechanism by which multiple factors interact with each other to affect smoking behaviors. Stress has long been recognized as a risk factor for smoking. However, the underlying mediation and moderation mechanisms are far from clear. The purpose of this study was to examine the role of negative emotions in mediating the link between stress and smoking and whether this indirect link was modified by resilience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 63 publications
3
20
2
1
Order By: Relevance
“…These smokers have no smoking limitation based on the type of their job and work restrictions, so they show higher smoking rates on days (28). In the present study, divorcees smoked more than singles and married individuals, regardless of their level of knowledge about the high-risk use of cigarettes, being consistent with the results of the studies by Ebadi et al (28) and Wang et al (29). To explain this briefly, one can say that when a person is divorced, who may have been compliant with their married life, they suddenly experience a lot of stress as well as loneliness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These smokers have no smoking limitation based on the type of their job and work restrictions, so they show higher smoking rates on days (28). In the present study, divorcees smoked more than singles and married individuals, regardless of their level of knowledge about the high-risk use of cigarettes, being consistent with the results of the studies by Ebadi et al (28) and Wang et al (29). To explain this briefly, one can say that when a person is divorced, who may have been compliant with their married life, they suddenly experience a lot of stress as well as loneliness.…”
Section: Discussionsupporting
confidence: 92%
“…In such cases, they may find it difficult to look after themselves, so they lose control of the affairs (30). The smokers aged over 50 smoke more than younger ones; however, no study was found to have reported the relationship between different age groups and cigarettes smoked per day (29,31). In the current study, the smoking rate increased with aging, and the smokers aged over 50 smoked more cigarettes; this implies that a long history of smoking has gradually affected the smoking rate; therefore, it turned into a habit, making it difficult for them to quit smoking (26).…”
Section: Discussioncontrasting
confidence: 57%
“…These findings suggested that the effective work stress management could not only decrease depressive symptoms directly but could also indirectly relieve it through nicotine dependence. In future, longitudinal design should be employed to examine whether depressive symptoms could predict nicotine dependence ( Lerman et al, 1996 ; Currie et al, 2001 ; Ong and Walsh, 2001 ; Dierker et al, 2015 ; Wang et al, 2016 ), and even more, whether nicotine dependence link the relationship between depressive symptoms and work stress.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, persons with severely depressive symptoms may have an increased risk of nicotine dependence ( Breslau et al, 1993 ; McKenzie et al, 2010 ; Trosclair and Dube, 2010 ; Scherphof et al, 2013 ). Some studies argue that nicotine dependence can predict depressive symptoms ( Brown et al, 2000 ; Loprinzi et al, 2014 ), while others insist that depressive symptoms increase a risk of nicotine dependence ( Lerman et al, 1996 ; Currie et al, 2001 ; Ong and Walsh, 2001 ; Dierker et al, 2015 ; Wang et al, 2016 ). The recent notion that comorbidity between nicotine dependence and depressive symptoms may reflect common factors related to both outcomes is widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, one of the psychological factors affecting smoking tendency is known as perceived stress, which can provide conditions for different mental and social problems (11). Experiences associated with regular criticism by parents or family members can also make a person agitated; moreover, most individuals are afraid of criticism and it is thought that this fear leads to punishment avoidance.…”
Section: Introductionmentioning
confidence: 99%